Determinants Of Tax Aggressiveness In Food And Beverage Sub Sector Companies Listed On The Indonesia Stock Exchange - Paskalina, Maria; ningsih, Murtia (International Journal of Educational Research & Social Sciences, 2022)
Taxes as a source of state revenue, state revenue plays an important role in national development. There are many obstacles in optimizing tax revenue, one of which is the form of non-compliance in tax payments, one of which is tax aggressiveness. This study was conducted to determine the effect of liquidity, profitability and leverage on tax aggressiveness in food and beverage companies listed on the IDX. In this study, tax aggressiveness is measured by the Effective Tax Rate (ETR), liquidity is measured by current assets and current liabilities, profitability is measured by the ROA (Return On Asset) indicator, leverage is measured by total debt and total equity. This research uses quantitative methods. The selected population is 30. The results of this study indicate that profitability has a positive effect on company aggressiveness, using the purposive sampling method, so that a sample of 12 companies for 3 years in 2018-2020 meet the criteria. The data were analyzed using multiple-tax linear regression, while liquidity and leverage had a negative effect on tax aggressiveness.